Maternal Perceptions of Alcohol Use by Adolescents Who Drink Alcohol - GUILAMO-RAMOS, VINCENT (2006)
OBJECTIVE: This research examines correlates of mothers’ misperceptions of their adolescent children’s regular alcohol consumption. Theories of adolescent autonomy, attribution processes, and stereotypes were used to make predictions about the biasing effects on attribution accuracy of maternal age, relationship satisfaction, and supervision of one’s adolescent, as well as the adolescent’s age, gender, physical development level, and peers. METHOD: The present research used a nationally representative sample of approximately 20,000 parent-adolescent dyads from the National Longitudinal Study of Adolescent Health (Add Health). Add Health is a school-based sample of 20,745 adolescents in Grades 7–12. Mothers indicated their perceptions of their adolescent children’s alcohol use, and adolescents reported their actual use of alcohol. RESULTS: There was a tendency for mothers to underestimate alcohol use, sometimes substantially so. Maternal attributions followed a correlational pattern consistent with the scientific literature. There was evidence, however, that mothers may overgeneralize the applicability of these correlates, resulting in misattributions. CONCLUSIONS: Our analyses have important practical implications for parent-based intervention programs aimed at preventing adolescent alcohol use. First, programs should alert parents to the cues that signify adolescent alcohol consumption. Second, intervention programs should appropriately sensitize parents to identifying adolescent alcohol use in cases in which the child may not fit the stereotype of an adolescent drinker. Third, intervention messages should emphasize firm and consistent parental actions that minimize alcohol use independent of the particular cues that an adolescent is projecting.